La importancia del nuevo rol de los padres en la educación inicial virtual - Alfaro, Piero Paúl (2021)
By finding Peruvian education in a state of crisis due to the global situation presen ted by Covid-19, it was considered important to investigate the new forms of initial education that are taking place in the country today, following the constraints of the global crisis. In this way, face-to-face education became virtual and thus the role of the parents was modified, we are taking a greater presence in the teaching of their children. With this, we decided to explore the perception of the parents of the initial students, between the age of 3 to 5 years, of private schools in Lima, about their role in the context of distance education. In this sense, the specific objectives are three: first, to describe the measures taken by the private schools of Lima to implement a distance education at the initial level; secondly, to describe the opinion of specialists on the role parents have taken with regard to this new education sys tem; and finally describe the views of parents about their institutional and personal experience in the face of initial distance education.